2017
DOI: 10.1002/chem.201702857
|View full text |Cite
|
Sign up to set email alerts
|

Buildup of Redox‐Responsive Hybrid from Polyoxometalate and Redox‐Active Conducting Oligomer: Its Self‐Assemblies with Controllable Morphologies

Abstract: A redox-responsive hybrid of polyoxometalate and conducting oligomer including its self-assemblies with controllable morphologies are reported. To this end, a hybrid molecule, containing a Lindqvist hexamolybdate as the polar head group and N,N'-bis(4'-amino-2,6-dimethylphenyl)-1,4-quinonediimine as the redox-responsive and aggregating group, is prepared. This hybrid exhibits redox-responsive behavior with controllable assembling morphological transition from spherical vesicles to short cylindrical vesicles. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…A system showing similar behaviour was developed by She et al . from a polyoxometallate (POM) coupled with a covalently linked tri(aniline).…”
Section: Switching Structurementioning
confidence: 87%
“…A system showing similar behaviour was developed by She et al . from a polyoxometallate (POM) coupled with a covalently linked tri(aniline).…”
Section: Switching Structurementioning
confidence: 87%
“…This discovery opens a new view of self-assembly systems based on polyoxometalates that could be used as conducting functional materials. 201…”
Section: Organoimido Derivatives Of Poms: Synthesis and Applicationsmentioning
confidence: 99%
“…This discovery opens a new view of self-assembly systems based on polyoxometalates that could be used as conducting functional materials. 201 John Fielden et al have investigated ten chromophores based on organoimido polyoxometalate (POM) and showed that imido-Lindqvist clusters are particularly effective acceptors in second-order NLO (nonlinear optical) materials when used with short ( phenyl) π-bridges. Here, the substituents on the aryl ring significantly impact the nature of electronic transitions in arylimido-POMs.…”
Section: Perspective Dalton Transactionsmentioning
confidence: 99%
“…POMs, synthesized from simple metal oxide salts, are inexpensive yet elegant structures that can be readily formed through one-pot self-assembly. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Among them, gigantic Molybdenum Blue (MB) wheel-shaped nanoclusters are of great importance in this area on account of their structural complexity and functional diversity. A certain number (n) of {Mo 8 } as main building blocks are connected together by the same number of {Mo 1 } and {Mo 2 } linkage units to form a nanowheel architecture, 28,29 exhibiting very high symmetries (e.g.…”
Section: Introductionmentioning
confidence: 99%